Impacts of the Victoria Nile Bujagali hydropower dam on fisheries and livelihoods. (17th January 2023) - Nduwayesu, Everest; Basooma, Anthony; Sekiranda, Stephen Kabali; Balirwa, John Stephen; Bassa, Samuel; Muhumuza, Elias; Mugeni, Bairon; Mulowoza, Alex; Musobya, Moses; Nakiyende, Herbert
Abstract: The Upper Victoria Nile (UVN) flows from Lake Victoria into Lake Kyoga, spanning 117 km and supports a diverse aquatic fauna that sustains livelihoods of riverside communities. The UVN is habitat to critically endangered ( Labeo victorianus ), near threatened ( Oreochromis variabilis and Oreochromis esculentus ), and rare species ( Neochromis simotes ). Four hydropower dams were built on the UVN to provide energy for industrial and socioeconomic development, notwithstanding consequential environmental and socioeconomic impacts. The impacts of Bujagali hydropower (BHP) dam on fisheries and livelihoods were assessed biannually (April and September) from 2006 to 2019, using fishing effort, species abundance, catch composition, and economic beach revenue at upstream, mid‐reservoir, and downstream transects. The fishing boats increased from 31 in 2009 to 293 in 2019 and fishers from 83 to 500 over the monitoring period. Maximum annual catch of 461.4 t was recorded in 2014 and lowest of 54.2 t in 2009. In all transects, Protopterus aethiopicus and Labeo victorianus were least in the commercial catches and the use of Mormyrus kannume juveniles as bait for Nile perch fishery corresponded with increased catches from 3.3 t in 2009 to 148.2 t in 2019. Women were mostly engaged in post‐harvest activities such as fish drying, smoking, and food vending. These observations suggest coupling effects of the hydropower dam and ineffective fisheries management. The harvest of M. kannume wild stocks for bait should be banned and research in possible domestication of the species undertaken. There is a need to strengthen fisheries enforcement to curb illegal effort and overexploitation and to implement conservation actions to mitigate potential biodiversity impacts from the hydropower dam operations.